Praktik Akad Syirkah Pembuatan Batu Bata Merah Menurut Perspektif Hukum Islam - Harahap, Titi Martini; Ardiansyah, Ardiansyah; Siregar, Erpiana (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
Jambur village is one of the villages that has saw land or land which is usually used as raw material for red bricks. The practice of the syirkah contract that occurs is that the land owner and the brick maker collaborate with a contract not in writing but verbally, then the land owner provides capital in the form of his empty land to be occupied as a place for making bricks while the manager manages the land for the bricks making process with land rental cost. Meanwhile, the distribution of sales proceeds is borne by the manager. This research aims to find out the process and views of Islamic law regarding the syirkah contract between land owners and brick managers in Jambur village, District North Panyabungan district Mandailing Natal. This research is field research (field research) with a descriptive qualitative approach using primary and secondary data sources. The author obtained primary data from interviews with land owners, brick managers, religious leaders and people related to this research. The results of the research show that the practice of syirkah contracts for making bricks in Jambur village, land owners receive rent for their vacant land and receive a mandatory percentage of the number of bricks produced. In Islamic law this is not permitted because it contains multiple contracts and is detrimental to the manager.